STRATEGY FOR STRENGTHENING FAITH FOR CONVERTS AT AR-RISALAH CONVERTS CENTER KERINCI DISTRICT, REGENCY PELALAWAN, RIAU PROVINCE - Hamidi, Fauzan (FORUM PAEDAGOGIK, 2025)
This study explores the roles, strategies, and challenges faced by the Muallaf Center Ar-Risaya in Kerinci District, Pelalawan Regency, Riau Province, in strengthening the Islamic creed (aqidah) of converts. The research highlights the significance of aqidah development as the initial foundation for building faith and facilitating social integration into Islamic life. Employing a qualitative field research design, data were collected through in-depth interviews, observation, and documentation involving institutional administrators, converts, and local community members. The findings reveal that the Muallaf Center Ar-Risala functions not only as a provider of theoretical understanding of aqidah but also as a supportive mentoring institution focusing emotional, social, and spiritual approaches. The strategies include routine study sessions, halaqah, practical worship training, open discussions, individual mentoring, and social strengthening through collective activities. Despite encountering obstacles such as diverse cultural and religious backgrounds, limited basic Islamic knowledge, and resource constraints, the center has demonstrated significant positive impacts on converts' understanding of Islam, self-confidence, and active participation in religious practices. This research underscores the importance of a comprehensive and humanistic approach to aqidah development in ensuring the sustainability of converts' Islamic faith and identity.